Intra-operative uterine scar condition and fetomaternal outcome in patients of previous lower segment caesarean section (LSCS) with scar tenderness - Gupta, Nidhi; Sinha, Renuka (International Journal of Research in Medical Sciences, 2017)
Background: During past few years, there is increasing trend in trial of labor in cases of previous lower segment caesarian section (LSCS). It needs vigilant approach in identifying signs and symptoms of giving way of previous scar. This study is to see the intra-operative uterine scar condition and feto-maternal outcome in patients of previous LSCS with scar tenderness. Methods: This is a prospective study done in Safdarjung hospital, New Delhi. It includes 120 patients of previous lower segment caesarian section with scar tenderness operated as emergency cases over a period of one year. It excludes elective repeat LSCS. Results: During this period repeat emergency LSCS was done in 862 cases and scar tenderness was seen in 120 cases (13.92 %). Out of 120 cases enrolled for the study intra-operative scar was intact in 69 cases (57.5%). Scar was thinned out in 27 cases (22.5%). Scar dehiscence was found in 21 cases (17.5%). Rupture occurred in 3 cases (2.5%) out of which 2 were Fresh still births. NICU admission was done in 11 cases (9.17%). 1 neonatal death occurred. No maternal death was recorded. Average hospital stay was 6 days. Blood transfusion was needed in 23 cases (19.2%). Conclusions: Scar tenderness is a very important tool for predicting scar integrity. All cases of previous LSCS should have institutional delivery.